Assessing the Sustainability Performance, the Food-Processing Industry through Causal Loop: A Mauritian case study (Global Journal of Science Frontier Research, 2023)
Sustainability has emerged as one of the megatrends in the food processing industries prevails as one of the most important items on the agenda of many companies The major sustainability domains environmental social and economic aspects are topics that companies are called to focus on nowadays for achieving success These include utilisation of resources such as water energy working conditions safety at work and investments among others This research work aims at assessing the sustainability performance of food processing organisations and propose sustainable practices with a focus on environmental social and economic The interactions of the sustainable practices from the causal loop diagrams have shown the importance of recycling and reusing of solid wastes water treatment investment in renewable energy and continuous improvement of practices and policies through audits Sustainable consumption and production campaigns through sustainability initiatives is very effective to reduce production intensity thus the use of resources
Keywords: sustainability; sustainability indicators; food processing industries; causal loop diagrams